2020
DOI: 10.3892/ol.2020.12398
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑200a and microRNA‑141 have a synergetic effect on the suppression of epithelial‑mesenchymal transition in liver cancer by targeting STAT4

Abstract: MicroRNAs (miRNAs or miRs) are non-coding small RNAs that target specific messenger RNAs to inhibit protein translation. miR-200a and miR-141 function as tumor suppressors by targeting STAT4. These two miRNAs belong to the same family, and their expression is often decreased in various cancer types, but are located on different chromosomes of the human genome. The present study showed that the expression levels of miR-141 and miR-200a in serum and cells of liver cancer are significantly downregulated. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In addition, downregulation of STAT4 has been reported for cutaneous T-cell lymphoma (CTCL) and was associated with progressed disease stages [44,45]. An immediate regulation of STAT4 by miR-141-3p via STAT4's 3 UTR has been demonstrated by luciferase reporter assays in various cellular systems (e.g., hepatocellular carcinoma) [46,47]. From this, we concluded the same direct regulatory relationships to underlie our observations in mature T-cell leukemia cells without explicitly validating these molecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, downregulation of STAT4 has been reported for cutaneous T-cell lymphoma (CTCL) and was associated with progressed disease stages [44,45]. An immediate regulation of STAT4 by miR-141-3p via STAT4's 3 UTR has been demonstrated by luciferase reporter assays in various cellular systems (e.g., hepatocellular carcinoma) [46,47]. From this, we concluded the same direct regulatory relationships to underlie our observations in mature T-cell leukemia cells without explicitly validating these molecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of the investigated miRNAs for diagnosing tumor invasion in liver cancer and comparing metastasis of patients with liver cancer were higher in combination of miR-141 and miR-200a rather than alone, although the difference between AUC values in both cases-combination and one miR regimen-had no significant changes. The possible mechanism of cancer processes modulation was explained with E-cadherin and vimentin inhibition due to STAT4 inhibition, which was firstly reported as a target gene for these miRNAs [89,90]. The study of Dhayat et al also showed a significant negative correlation of miR-200a and miR-200b to the expression of the mesenchymal markers Vimentin and ZEB-1 and a significant positive correlation to the epithelial marker E-cadherin.…”
Section: Differential Expression Of Mirnas In Hccmentioning
confidence: 99%
“…This family of miRNAs may be divided into two clusters according to the location on the chromosomes [21,22]. The nucleotide sequence of miR-141 is located on chromosome 12p13.31 and it recognizes the nucleotide sequence 5 -AACACUG-3 on the target mRNAs [23]. Mature miR-141 appears in two different forms: miR-141-3p and miR-141-5p depending on the orientation of the origin strand [21].…”
Section: Biogenesis Of Mir-141 Circrnas and Importance Of Their Inter...mentioning
confidence: 99%